Initial Understanding and Practice of Network Services and Compositions - Dongnian Cheng; Yufeng Li; Hailong Ma; Wanwei Huang (Dianxin kexue)
The current internet is simple in its fundamental interconnecting capability and is inflexible in its protocol architecture.Such a situation makes internet unable to well handle the variety of network applications' demands.Fortunately,a noval approach of so called“network service composition”can address the above problems.From the rationale of reductionism,the meanings of network services and their compositions were first explained.Several fundamental and key methods of network service composition were then presented,with relevent research projects shown.And finally,the ongoing work in the reconfigurable architecture of network infrastructures was introduced.